Steroid sulfatase and sulfuryl transferase activity in monkey brain tissue - Kríz, Lubomír; Bicíková, Marie; Hill, Martin; Hampl, Richard (Steroids, 2005)
Dehydroepiandrosterone and its sulfated form are commonly known as modulators of gamma-aminobutyrate A and N-methyl-D-aspartate receptors. In spite of poor permeability of the blood-brain barrier for sulfated steroids, high concentrations of dehydroepiandrosterone and also its sulfate have been found in brain tissue. Physiological concentrations of these neuromodulators are maintained by two enzymes present in the blood and many peripheral tissues, including the brain, namely, steroid sulfatase and neurosteroid sulfuryl transferase (NSST). This prompted us to investigate activities of these enzymes in primate brain tissue. Rather low neurosteroid sulfuryl transferase activity was detectable in in vitro incubations of cytosol fractions from male and female Macaca mulatta brains, dissected to cerebral cortex, subcortex, and cerebellum. In male monkeys, the highest activity was found in the cerebellum followed by cortex and subcortex. On the other hand, in female monkeys, the highest activity was determined in the cortex followed by subcortex and cerebellum. Steroid sulfatase activity was determined in in vitro microsomal samples from each of the above-mentioned brain regions. Specific activities in female cerebral regions declined in the order: cerebellum, cortex, and subcortex. In male monkeys, no significant difference among the studied regions was observed. Using dehydroepiandrosterone sulfate as a substrate, the apparent kinetic characteristics of steroid sulfatase were determined as follows: K(M) 36.10 +/- 8.33 microM, V(max) 8.38 +/- 1.68 nmol/h/mg protein. These results will serve as a basis for further studies concerning the pathophysiology of human brain tumors.
Keywords: koncentrace vodíkových iontů; steryl-sulfatasa; Time Factors; Macaca mulatta; zvířata; Male; Female; biotest; Mass Spectrometry; Hydrogen-Ion Concentration; Sulfur Group Transferases; Biological Assay; Steryl-Sulfatase; Animals; mozek; mužské pohlaví; hmotnostní spektrometrie; ženské pohlaví; transferasy přenášející skupiny obsahující síru; časové faktory; Temperature; Brain; teplota; mozek - chemie; Brain Chemistry